2021
DOI: 10.3892/etm.2021.9714
|View full text |Cite
|
Sign up to set email alerts
|

Association between vascular comorbidity and glaucoma progression: A four-year observational study

Abstract: Glaucoma, one of the significant causes of blindness worldwide, is a chronic optic neuropathy, characterized by progressive loss of retinal ganglion cells and specific perimetric defects. This study aimed to assess the association between the risk of glaucoma progression and different systemic vascular abnormalities. A 4-year prospective study was carried out on 204 patients diagnosed with open-angle glaucoma. Associated systemic vascular pathology was documented in 102 cases. Progression was encountered in 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…59 The PLTP gene encodes the lipid transfer protein, which transfers lipopolysaccharides, α-tocopherol, diacylglycerol, cerebroside and may contribute to the development of metabolic syndrome, insulin resistance, obesity, atherosclerosis, and type II diabetes, etc.. 60 There is evidence that systemic comorbidities associated with hyperglycemia, hyperlipidemia, endothelial lesions, and atherosclerosis can lead to damage to the retinal nerve fiber layer and the underlying conjunctive tissue. 1,61,62 Besides, PLTP may be involved in signal transduction pathways in human neurons 63 and may contribute to maintaining integrity of the blood-brain barrier, possibly through its involvement in transfer of vitamin E and modulation of the cerebrovascular oxidative stress. 64 One more candidate gene for POAG suggested by the in silico analysis, SLC12A5 , modulates Ca 2+ -dependent insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…59 The PLTP gene encodes the lipid transfer protein, which transfers lipopolysaccharides, α-tocopherol, diacylglycerol, cerebroside and may contribute to the development of metabolic syndrome, insulin resistance, obesity, atherosclerosis, and type II diabetes, etc.. 60 There is evidence that systemic comorbidities associated with hyperglycemia, hyperlipidemia, endothelial lesions, and atherosclerosis can lead to damage to the retinal nerve fiber layer and the underlying conjunctive tissue. 1,61,62 Besides, PLTP may be involved in signal transduction pathways in human neurons 63 and may contribute to maintaining integrity of the blood-brain barrier, possibly through its involvement in transfer of vitamin E and modulation of the cerebrovascular oxidative stress. 64 One more candidate gene for POAG suggested by the in silico analysis, SLC12A5 , modulates Ca 2+ -dependent insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of logistic regression analysis, we found that experiencing migraines significantly influences the diagnosis of OHT vs. OAG. Peripheral vasospasm is vascular dysregulation (altered vasoconstriction and/or vasodilation) of the microvasculature that is manifests as symptoms of cold hands and feet [ 73 ] and is associated with glaucoma risk and progression [ 74 , 75 ]. We identified this symptomatology in 25% of our OHTG and 31% of our OAGG populations.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is a devastating optic neuropathy afflicting millions worldwide, and yet the complex etiology of the disease results in the ensuing neurodegeneration not receiving effective treatment for many individuals. While the past understanding and treatment of the disease has focused on controlling IOP, the only current modifiable risk factor, recent research has elucidated a substantial contribution of retinal vasculature dysfunction to disease progression [ 3 , 7 , 9 , 34 ]. Whether vascular dysfunction occurs early in glaucoma triggering neurodegenerative events, or whether RGC degeneration leads to the disruption of NVC remains challenging to determine.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma shares comorbidities with a number of systemic vascular diseases, including diastolic hypotension, diabetes, ischemic cardiac disease, peripheral vasospasm, and arterial hypertension [ 7 , 8 ]. Advances in vascular imaging technology have provided evidence of a link between vascular dysfunction and glaucoma in both animal models and in the clinic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%